Potential Use of Haematopoietic or Mesenchymal Stem Cells in the Treatment of Immune Mediated Neutropenia in Domestic Canines - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
In domestic canines, neutrophils are the major component of white blood cells, which when reduced in numbers (neutropenia) can significantly compromise innate immune physiology. Several conditions are known to cause neutropenia in canines, however when neutropenia is observed without any underlying cause, it is suspected to be immune mediated neutropenia (IMN). Although IMN is treated symptomatically using immunosuppression therapy, the recent developments in stem cell therapies offer therapeutic potential especially in IMN cases which relapse. This brief report outlines the merit of haematopoietic (HSC) and/or mesenchymal (MSC) stem cells in the treatment of IMN in domestic canines. The known efficacy of HSC to repopulate the stem cell niche responsible for production of neutrophils in bone marrow together with the immunomodulatory properties of MSC can be therapeutic against IMN. Such innovative stem cell based therapies for IMN in domestic canine’s merits clinical evaluation.
Keywords: Neutropenia; Stem cell disease; Autoimmune; Myeloid cells; Cell therapy